The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1094/pdis.2002.86.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to QoI (Strobilurin-like) Fungicides in Isolates of Pyricularia grisea from Perennial Ryegrass

Abstract: In August 2000, azoxystrobin was ineffective in controlling gray leaf spot of perennial ryegrass at a golf course in Lexington, KY and at two golf courses in Illinois. Isolates suspected of being fungicide-resistant (“suspect isolates”) were compared to “baseline” isolates obtained from sites with no known use of quinol-oxidizing inhibitor (QoI) fungicides. Conidial germination of Pyricularia grisea was tested in vitro with 100 μg of salicylhydroxamic acid per ml. For baseline isolates, 50% effective concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 13 publications
2
63
0
1
Order By: Relevance
“…Several studies document those different fungicides once highly effective in suppressing P. infestans before the 1980s have now lost their efficacy of controlling late blight in different parts of the world (Goodwin et al, 1998;Yuan et al, 2006). Vincelli and Dixon (2002) argues that there are two types of resistance development -qualitative and quantitative-in pathogen towards fungicides. In quantitative resistance, new variants show comparatively less sensitivity to fungicides than their parental types.…”
Section: Reasons For Resistance Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies document those different fungicides once highly effective in suppressing P. infestans before the 1980s have now lost their efficacy of controlling late blight in different parts of the world (Goodwin et al, 1998;Yuan et al, 2006). Vincelli and Dixon (2002) argues that there are two types of resistance development -qualitative and quantitative-in pathogen towards fungicides. In quantitative resistance, new variants show comparatively less sensitivity to fungicides than their parental types.…”
Section: Reasons For Resistance Developmentmentioning
confidence: 99%
“…This type of resistance can be overcome by increasing the dose and spray frequency of fungicides. On the other hand in qualitative resistance, progenies show greater resistance to fungicides than their parents and cannot be compromised by increasing dose rate and frequency of fungicide spray (Vincelli and Dixon, 2002). Reports of increased number of isolates and cases of resistance development to fungicides are generally assigned to the appearance of new genotypes.…”
Section: Reasons For Resistance Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds belong to the group of the quinone outside inhibitors (QoI) or group 11 fungicides, whose toxicity arises from the inhibition of the mitochondrial respiratory chain at Complex III level, preventing the biochemical chain of electron transfer at the site of mitochondria, interfering with respiration of the pathogen (Ghini & Kimati 2000). They are typically absorbed by the cuticle of the fungus, acting as protectant fungicides (Vincelli & Dixon, 2002).…”
Section: Chemical Control Of Cotton Bolls Rotmentioning
confidence: 99%
“…21) Moreover, azoxystrobin and trifloxystrobin were used to control ryegrass disease caused by P. grisea, however, the two strobilurin fungicides lost its efficacy in controlling P. grisea. 30) In Taiwan, strobilurin fungicides are commonly used for controlling powdery or downy mildew of cucumber, downy mildew of crucifer, late blight of tomato and potato, rust disease of allium, anthracnose of fruits and other fungal diseases of fruits. 22) Previous studies demonstrated that the isolates of Botrytis cinerea from strawberry and Colletotrichum gloeosporioides from mango and strawberry showed low sensitivity to kresoxim-methyl, azoxystrobin and triflorstrobin.…”
Section: Introductionmentioning
confidence: 99%